Significance of ST Segment Elevation in Lead aVR in Patients with Non-ST Elevation Acute Coronary Syndrome - Gachchhadar, Pritam Kumar; Mahmood, Manzoor; Adhikary, Dipal Krishna; Chowdhury, MSI Tipu; Sultan, Md Ashraf Uddin; Mandal, MRM; Md Iqbal, Khaled; Banerjee, Sajal Krishna (University Heart Journal, 2019)
Background: As acute occlusion of the left main (LM) artery causes life-threatening hemodynamic deterioration and malignant arrhythmias, resulting in an adverse outcome, a rapid diagnosis and subsequent urgent revascularization with percutaneous coronary intervention (PCI) or coronary bypass surgery is very important in this subset of patients. The 12-lead electrocardiogram (ECG) is a crucial tool in the diagnosis and risk stratification of acute coronary syndrome (ACS). Unlike other 11 leads, lead aVR has been long neglected until recent years. Objective: To determine the accuracy of 12-lead electrocardiography in predicting left main and/or triplevessel disease in patients with non-ST elevation acute coronary syndrome (NSTE- ACS). Methodology: This cross sectional observational study carried out among patients presenting with non-ST elevation acute coronary syndrome at Cardiac Emergency Department or CCU of BSMMU. This study was conducted from May 2017 to April 2018. A total of 36 patients meeting the eligibility criteria were consecutively included. Data collection was carried out by using a questionnaire. Informed written consent was obtained from the hospital authority. Analysis of data was finally done with Statistical Package for Social Science program 17 version of computer on the basis of different variables. Result: As ST-segment elevation in lead aVR is a continuous variable, a suitable cut-off for ST- elevation in lead aVR was found out for diagnosing LM and/or triple vessel disease (TVD) using ROC curve. The cut-off value was 0.75 mm which gave us an optimum sensitivity of 88.5% and a specificity of 80% with an area under the curve being 0.892(95% CI = 0.785-1.000), p < 0.001. The area under the curve demonstrated that 89.2% of the LM and/or TVD were correctly diagnosed with ST elevation e” 0.75 mm in lead aVR in patients with non-ST segment elevation acute coronary syndrome. The positive predictive value was commendably high (92%) and negative predictive value was no less (72.7%) with an overall diagnostic accuracy of 86%. Conclusion: From the findings of the study it can be concluded that ST- segment elevation e”0.75 mm in lead aVR in patients of non-ST segment elevation acute coronary syndrome had optimum sensitivity and specificity with an appreciably high overall diagnostic accuracy. The ST- segment elevation e”0.75 mm in lead aVR in patients with non-STE-ACS can differentiate LM and/or triple vessel disease with fair degree of accuracy. University Heart Journal Vol. 14, No. 2, Jul 2018; 71-76